Insects and other arthropods of tropical America - Hanson, Paul E.; Nishida, Kenji, 1972- (Ithaca : Comstock Publishing Associates, a division of Cornell University Press, 2016)
"Describes the principal insect groups and other arthropods encountered in a tropical forest in the Americas, and is an introduction to the natural history of insects and other arthropods"--
Introduction to arthropods -- Small orders -- True bugs and their kin -- Beetles -- Wasps, bees, ants -- Moths and butterflies -- Flies and their kin -- Other arthropods.
"A Zona Tropical publication."
Includes bibliographical references and index.
Keywords: Insects -- Latin America; Insects -- Tropics; Arthropoda -- Latin America; Arthropoda -- Tropics